2010
DOI: 10.1002/emmm.201000083
|View full text |Cite
|
Sign up to set email alerts
|

Correction of β‐thalassemia major by gene transfer in haematopoietic progenitors of pediatric patients

Abstract: β-Thalassemia is a common monogenic disorder due to mutations in the β-globin gene and gene therapy, based on autologous transplantation of genetically corrected haematopoietic stem cells (HSCs), holds the promise to treat patients lacking a compatible bone marrow (BM) donor. We recently showed correction of murine β-thalassemia by gene transfer in HSCs with the GLOBE lentiviral vector (LV), expressing a transcriptionally regulated human β-globin gene. Here, we report successful correction of thalassemia major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
73
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 42 publications
5
73
0
2
Order By: Relevance
“…These observations represent a strategic issue, particularly in the view of the future use of gene therapy for b-Thalassemia, since it is now evident that in patients affected by hemoglobinopathies, few donor normal engrafted cells are able to correct the genetic defect after HSCT. 19,20 References of donor type hematopoiesis present in the recipient. 9 It is likely that most of the patients with large amounts of RHCs early after HSCT face a prompt immunological reaction against the donor cells, although it has been shown that occurrence of transient MC does not necessarily lead to graft rejection.…”
Section: -3mentioning
confidence: 99%
“…These observations represent a strategic issue, particularly in the view of the future use of gene therapy for b-Thalassemia, since it is now evident that in patients affected by hemoglobinopathies, few donor normal engrafted cells are able to correct the genetic defect after HSCT. 19,20 References of donor type hematopoiesis present in the recipient. 9 It is likely that most of the patients with large amounts of RHCs early after HSCT face a prompt immunological reaction against the donor cells, although it has been shown that occurrence of transient MC does not necessarily lead to graft rejection.…”
Section: -3mentioning
confidence: 99%
“…It is noteworthy that such phenotypic improvement was achieved with a VCN of 1. The use of b-globin LCR elements for b-globin expression in thalassemic patient samples has been documented before, 5,20 but our study constitutes the first report on the successful use of the a-globin HS40 regulatory element for the functional correction of b-thalassemia in human primary samples.…”
Section: Evaluation Of B-globin Fv Vectors In Human Thalassemic Hscsmentioning
confidence: 85%
“…2,3 The HS2 and HS3 are the minimum regulatory sequences required for efficient expression of the b-globin gene in the Hbb th3/+ mouse model of b-thalassemia and in patient samples. 4,5 The discovery of the a-globin locus HS40 enhancer provided an alternative regulatory element for the expression of globin genes with variable success. [6][7][8] In this study, we have used foamy virus (FV) vectors, 9 a nonpathogenic genus of retroviruses, to provide a detailed comparison of the a-globin HS40 sequence and the b-globin LCR HS2 and HS3 sequences for the efficient expression of human b-globin gene.…”
mentioning
confidence: 99%
“…Gene therapy, in the form of transplantation of gene-corrected autologous or allogeneic cell populations, is an alternative therapeutic approach for treating inherited diseases with a monogenic defect, 3,4 such as sickle cell disease (SCD) and b-thalassemia, 5,6 severe combined immunodeficiency, 7 Fanconi anemia (FA), 8 and X-linked adrenoleukodystrophy (ALD). 9,10 Autotransplantation of stem cells expressing the therapeutic transgene overcomes the lack of a suitable allogeneic donor and eliminates the risks of graft-versushost disease and prolonged immunodeficiency that are associated with allogeneic BMT.…”
Section: Obstacles In Development Of Cell-based Therapies For Congenimentioning
confidence: 99%